Class and Caste in the 2019 Indian Election–Why Do So Many Poor Have Started to Vote for Modi?. (December 2019) - Jaffrelot, Christophe
In the 2009 and 2014 elections, the poorer the voters were, the less BJP-oriented they were too. The situation changed in 2019, when the prime minister appeared to be equally popular among all the strata of society, including the poor. Modi's massive appeal to the poor is counterintuitive given the weakening of pro-poor policies like the National Rural Employment Guarantee Act and the elitist character of BJP. If class has lost some of its relevance for explaining the results of the 2019 elections, caste is showing some resilience, not as aggregates in the garb of OBCs or SCs, but as jatis at the state level. In spite of the BJP's claim that the party's ideology was alien to any consideration which may divide the nation, its strategists have meticulously studied caste equations at the local level in order to select the right candidates. This caste-based strategy partly explains the above-mentioned class element as the small OBC and Dalit jatis that the BJP has wooed are often among the poorest—and upper caste poor vote more for BJP than their co-ethnic rich anyway.